2017
DOI: 10.1111/jcmm.13189
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MALAT1 is dysregulated in diabetic nephropathy and involved in high glucose‐induced podocyte injury via its interplay with β‐catenin

Abstract: Metastasis associated lung adenocarcinoma transcript 1(MALAT1) is a long non‐coding RNA, broadly expressed in mammalian tissues including kidney and up‐regulated in a variety of cancer cells. To date, its functions in podocytes are largely unknown. β‐catenin is a key mediator in the canonical and non‐canonical Wnt signalling pathway; its aberrant expression promotes podocyte malfunction and albuminuria, and contributes to kidney fibrosis. In this study, we found that MALAT1 levels were increased in kidney cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
143
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(146 citation statements)
references
References 56 publications
3
143
0
Order By: Relevance
“…Because siRNA mainly exert their gene‐silencing effects in cytoplasm, the RNA interference in nuclei does not seem as effective as in cytoplasm. However, in some studies, siRNA were utilized to silence lncRNA and mRNA expression in the nuclei, and the downstream genes and effects were efficaciously regulated . In our study, the TPT1‐AS1 depletion EOC cell lines were constructed by siRNA transfection, and were further utilized for in vitro function experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because siRNA mainly exert their gene‐silencing effects in cytoplasm, the RNA interference in nuclei does not seem as effective as in cytoplasm. However, in some studies, siRNA were utilized to silence lncRNA and mRNA expression in the nuclei, and the downstream genes and effects were efficaciously regulated . In our study, the TPT1‐AS1 depletion EOC cell lines were constructed by siRNA transfection, and were further utilized for in vitro function experiments.…”
Section: Discussionmentioning
confidence: 99%
“…However, in some studies, siRNA were utilized to silence lncRNA and mRNA expression in the nuclei, and the downstream genes and effects were efficaciously regulated. [41][42][43][44] In our study, the TPT1-AS1 depletion EOC cell lines were constructed by siRNA transfection, and were further utilized for in vitro function experiments. As the results showed, the knockdown efficiency of TPT1-AS1 was approximately 30%-40%, and the downregulation of TPT1-AS1 dramatically attenuated EOC cell proliferation, migration and invasion ability, and promoted cell adhesion ability, which are significantly opposite to the oncogenic effects of TPT1-AS1 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, lncRNAs have been identified to play a regulatory role in the pathogenesis of diabetic kidney diseases . Growing evidences have shown that a variety of lncRNAs are involved in DN . LncRNA GAS5, encodes a complicated repertoire of alternatively‐spliced lncRNA isoforms and is a host gene of numerous small nucleolar RNAs, which are processed from its introns .…”
Section: Introductionmentioning
confidence: 99%
“…9 Growing evidences have shown that a variety of lncRNAs are involved in DN. 10,11 LncRNA GAS5, encodes a complicated repertoire of alternatively-spliced lncRNA isoforms and is a host gene of numerous small nucleolar RNAs, which are processed from its introns. 12 The reduced expression of GAS5 has been reported to be associated with the occurrence of type 2 DM.…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence suggest that lncRNAs are involved in the pathogenesis of podocyte injury. Hu et al (7) reported that the level of the lncRNA MALAT1 was elevated in diabetic nephropathy and was involved in high glucose-induced podocyte injury via its interplay with ␤-catenin. Long et al (8) reported that Tug1 regulates mitochondrial function in podocytes by the epigenetic targeting of the transcription factor peroxisome proliferator-activated receptor ␥ coactivator 1␣.…”
mentioning
confidence: 99%